Focus groups: from structured interviews to collective conversations - Kamberelis, George (London : Routledge Taylor and Francis Group, 2020)
Focus From Structured Interviews to Collective Conversations is a conceptual and practical introduction to focus group. As the title indicates, focus groups traditionally encompass a wide range of discursive practices. These span from formal structured interviews with particular people assembled around clearly delimited topics to less formal, open-ended conversations with large and small groups that can unfold in myriad and unpredictable ways. Additionally, focus groups can and have served many overlapping purposes-from the pedagogical, to the political, to the traditionally empirical. In this book, focus groups are systematically explored; not as an extension or elaboration of interview work alone, but as its own specific research method with its own particular affordances.
Includes index.
Keywords: Evolution of focus groups; Analyzing focus group data; Groups in social science research